Women in the penal system according to the Bangkok rules - Kovačević Milica (Temida)
In the introduction of the paper the author refers to the position of women in the criminal justice system, which implies that special rules should be applied with respect to the specific needs of girls and women. In the central part of the paper, the author analyzes the Bangkok Rules (UN Rules for the Treatment of Women Prisoners and Non-custodial Measures for Women Offenders), that were adopted in 2010. This is the first international document that identifies, in a comprehensive and systematic manner, specific factors of female crime and special needs of women and mothers, which implies that it has a pivotal role in the system composed of other United Nations documents. Finally, the author concludes that the real improvement of the position of women in the penal system will take a lot more effort and resources and that the adoption of the rules is not sufficient.